2021
DOI: 10.1002/jmri.27574
|View full text |Cite
|
Sign up to set email alerts
|

Joint‐adjacent Adipose Tissue by MRI is Associated With Prevalence and Progression of Knee Degenerative Changes: Data from the Osteoarthritis Initiative

Abstract: Background: Adipose tissue has recently gained interest as an independent imaging biomarker for osteoarthritis. Purpose: To explore 1) cross-sectional associations between local subcutaneous fat (SCF) thickness at the knee and the extent of degenerative changes in overweight and obese individuals and 2) associations between local fat distribution and progression of osteoarthritis over 4 years. Study Type: Retrospective cohort study. Population: 338 obese and overweight participants from the Osteoarthritis Init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…We evaluated local SCF adjacent to the knee joint. A previous study found significant cross-sectional and longitudinal association between joint-adjacent SCF (mostly lateral) and semi-quantitative and quantitative imaging markers of knee OA [ 14 ]. How local adipose tissue around the knee – other than the IPFP – affects synovial inflammation on a cellular and cytokine level and how this is different to systemic effects of adiposity could be a focus of future investigations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We evaluated local SCF adjacent to the knee joint. A previous study found significant cross-sectional and longitudinal association between joint-adjacent SCF (mostly lateral) and semi-quantitative and quantitative imaging markers of knee OA [ 14 ]. How local adipose tissue around the knee – other than the IPFP – affects synovial inflammation on a cellular and cytokine level and how this is different to systemic effects of adiposity could be a focus of future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…2 ). Anterior measurements were performed perpendicularly anterior to the patellar tendon at half of its length in sagittal views of 3D DESS sequences [ 14 ]. The lateral and medial tibial spine served as anatomical landmarks to choose coronal and sagittal cross-sections, respectively, for reproducible measurements.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies reported that SCF thickness was significantly higher in individuals presenting with chondromalacia, 6 increases in thigh SCF over 2 years were associated with the progression of knee OA in men, 7 and greater joint-adjacent SCF levels at baseline were associated with higher odds for cartilage and meniscal structural progression over 4 years, independent of baseline BMI. 8 Thus, understanding the impact of localized adipose changes on adjacent knee joint tissue may provide novel insights OA pathogenesis, that are beyond the systemic effects of overall weight change.…”
Section: Introductionmentioning
confidence: 99%